Interaction study of the effects of environmental exposure and gene polymorphisms of inflammatory and immune-active factors on chronic obstructive pulmonary disease - Rui Wang; Yuanyuan Li; Yuting Jiang; Xiaona Liu; Hongqi Feng; Zhe Jiao; Bingyun Li; Chang Liu; Yuncheng Shen; Fang Chu; Chenpeng Zhu; Dianjun Sun; et al. (Respiratory Research)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a heterogeneous disease, influenced by both environmental and genetic factors. Single nucleotide polymorphism (SNP) in the human genome may influence the risk of developing COPD and the response to treatment. We assessed the effects of gene polymorphism of inflammatory and immune-active factors and gene-environment interaction on risk of COPD in middle-aged and older Chinese individuals. Methods In this community-based case–control study, 471 patients with COPD and 485 controls aged 40–76 years in Heilongjiang Province, China were included. Face-to-face interviews, lung function tests, and multiplex polymerase chain reaction were used to obtain data. Logistic regression model, generalized multifactor dimensionality reduction and crossover analysis were used to analyse the effects of SNPs, gene–gene interactions, and gene-environment interactions on COPD. Results CRP gene[rs1130864-A allele (OR, 1.77; 95% CI 1.11–2.81); G/A + A/A genotype (OR, 1.75; 95% CI 1.07–2.84)], FCAR gene[rs4806606-G (OR, 0.72; 95% CI 0.53–0.98); rs8112766-G (OR, 0.79; 95% CI 0.64–0.98)] and FCGR2A gene[rs4656308-C (OR, 0.74; 95% CI 0.55–1.00); rs4656309-T (OR, 0.81; 95% CI 0.66–0.99)] are independent influential factors for COPD. Rs1205 [RERI: 0.15 (0.07–1.00)] and rs1130864 [RERI: 2.45 (0.73–4.18)] of CRP gene, rs11084376 [OR: 0.54 (0.29–0.97)] of FCAR gene, rs844 of FCGR2B [SI: 0.30 (0.11–0.77); OR: 0.46 (0.24–0.90)] gene, rs4656308-rs4656309-rs2165088 haplotype [SI: 0.48 (0.26–0.89)] of FCGR2A gene and exposure to smoking index > 200, indoor coal/wood/straw use, and outdoor straw burning play synergistic or antagonistic roles in the development of COPD. Conclusions Alleles and genotypes of the CRP/FCAR/FCGR2A gene can increase the susceptibility to COPD in the northern Chinese population. For the first time, environmental exposure to the CRP/FCAR/FCGR2A/FCGR2B genes has been shown to have synergistic or antagonistic effects on COPD susceptibility on genotypes or haplotypes.